C1B domain peptide of protein kinase Cγ significantly suppresses growth of human colon cancer cells in vitro and in an in vivo mouse xenograft model through induction of cell cycle arrest and apoptosis - Kawabata, Atsushi; Matsuzuka, Takaya; Doi, Chiyo; Seiler, Garret; Reischman, Jennifer; Pickel, Lara; Ayuzawa, Rie; Nguyen, Thu A.; Tamura, Masaaki (My University, 2012)
Two peptides derived from the C1B domain of protein kinase Cγ (PKCγ) were shown to associate with classical PKC isozymes and modulate their activities. These C1B peptides are designated C1B1 (amino acid residues 101-112) and C1B5 (residues 141-151). Since PKC enzyme activity is shown to be involved in colon cancer development, the effect of C1B peptides on the growth of various human colon cancer cell lines was examined in vitro and in vivo. Sub-micromolar to micromolar levels of both C1B peptides induced approximately 60-70% growth attenuation in multiple colon cancer cell lines in a soft agar tumor colony assay; however, C1B5 peptide was not cytotoxic to normal colon epithelial cells in two dimensional culture. The effect of C1B5 peptide on colony growth of COLO205 cells was reversed by treatment with the PKCα/β inhibitor, Ro-32-0432. C1B peptide treatment attenuated COLO205 cells via two mechanisms: 1) cell cycle arrest and 2) stimulation of apoptosis. This is evident in G[subscript ⁯2] arrest and increases in levels of cleaved caspase 3 and p53 phosphorylated at serine 20. Intratumoral injection of C1B5 peptide (20 mg/kg/day, every three days) markedly attenuated the growth of subcutaneous xenografts of COLO205 cells in SCID mice by 76% compared to the control. Taken together, these results strongly suggest that C1B peptides have negligible effects on normal tissues but are potentially effective chemotherapeutic agents for colon cancer.
Keywords: Protein kinase Cγ (PKCγ); C1B domein peptides; Colon Cancer; C1B domain; Xenograft; COLO205 colon carcinoma cells; Cancer therapy; PKCα/βII